Remote Sensing Applications in Agricultural, Earth and Environmental Sciences - Romano Lottering; Kabir Peerbhay; Samuel Adelabu (Applied Sciences)
Remote sensing has become an essential tool in agricultural, earth and environmental sciences and offers significant insights into land use changes, climate variability, and resource management [...]